A força motriz das organizações : potencializando a capacidade tecnológica através da gerência inovadora - Figueiredo, Paulo N. (1993)
This Dissertation tries to demonstrate the viability of enabling the developing countries business organizations - mainly the Brazilian ones - to operate under the knowledge-intensive pattem of competitiveness. depite the structural disadvantages of these countries'economy. Based upon the strategy of strengthening technological capacity in organizations. such a proposition is proved through the application of the theory of contemporary management combined with organizational practitioners'experiences and with empirical evidences found by interviewing executives from 28 organizations. Firstly. the contemporary meaning of technology, under organizational perspective, is discussed and the main externaI environmental changes which influences on the management of technological capacity in organizations are analysed. Secondly, two strategies seen as viable to strengthen technological capacity in organizations are formulated: i) technological leaming and organizational capability and ii) modalities of inter-company technological cooperation, with emphasis • upon the management of international joint-ventures. Finally, the study comes to the conclusion that despitethe institutional and persistent economic crisis visible in Brazilian economy, companies engaged in processes of technological capability - according to the strategies formulated here - can be found. Such evidences support the viability of these strategies as well as makes them useful to organizations which intend to upgrade their management systems to cope with the new technological trends.